Functional control in physical education of medical students - Kadomtseva E.M.; Ponomarev V.V.; Zhernakov D.V.; Poboronchuk T.N. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to theoretically substantiate and develop operational functional monitoring of the physical condition of medical university students based on their heart rate in a standing position (at rest), which will allow for a differentiated approach to regulating students’ physical activity during physical education. Methods and structure of the study. The study was conducted from 2024 to 2025 at the Krasnoyarsk State Medical University. The sample size was 800 1st-2nd year students. The following research methods were selected to collect scientific data: analysis of scientific and methodological literature, questionnaires, physical fitness testing, pedagogical observation, surveys, measurement of heart rate while standing during practical classes and in general over the course of a year, mathematical statistics, etc. The collected and systematised scientific and practical material contributed to the development of levels of functional readiness of medical university students based on heart rate in a standing position (at rest), which allows for the rapid monitoring and regulation of students’ physical activity during physical education. Results and conclusions. Based on the results of scientific and practical work, levels of functional readiness (high, medium, and low) of students for physical activity were developed based on monitoring heart rate in a standing position (at rest). This functional monitoring allows for the rapid assessment of students’ psychophysical condition during physical education classes and timely adjustments to the teaching process. All this contributes to a differentiated approach to students’ physical activity depending on their initial functional condition and timely adjustment of the physical condition of those involved in physical education.